An implementation of a statistical language based on JAVA - Takeshi Fujiwara; Junji Nakano; Yoshikazu Yamamoto; Ikunori Kobayashi (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
As computing technologies have been developed rapidly and continuously, statistical languages should be frequently improved by adopting them for realizing comfortable statistical environments. Although that work was a difficult task before we can implement such languages relatively easily by modern software techniques such as the Java language which unifies recent computer technologies widely and neatly. In this paper, we describe the idea of a new Jasp (JAva based Statistical Processor) language, which is a function based and object oriented language) is suitable for interactive operation and has flexibilities and diverse extendibilities. Considering required characteristics for a statistical language, we decide to implement the Jasp language by Java technologies through the Puuts language, which is a script language written in Java and a preprocessing approach. This implementation brings several advantages such as reduction of development costs, effective uses of existing resources and enough reliabilities.
urn:nbn:de:kobv:11-10050444
Keywords: 330; Java; Function based language; GUI; Object oriented language; Preprocessing; Statistical System